Post-transplant cyclophosphamide pharmacokinetics and haploidentical hematopoietic cell transplantation outcomes: an exploratory study. Issue 11 (19th September 2022) - Kasudhan, Kripa Shanker; Patil, Amol N.; Jandial, Aditya; Khadwal, Alka; Prakash, Gaurav; Jain, Arihant; Bhurani, Dinesh; Ahmed, Rayaz; Agrawal, Narendra; Singh, Reema; Sachdeva, Man Updesh Singh; Varma, Neelam; et al.
Abstract: Pharmacokinetics of cyclophosphamide has been explored to optimize conditioning dosing. We hypothesized that post-transplant cyclophosphamide (PTCy) metabolite carboxy-ethyl phosphoramide mustard (CEPM) pharmacokinetics might impact haploidentical transplantation (haplo-HCT) outcomes. CEPM area under the curve (AUC0–48 ) was determined by eleven sampling timepoints on day +3/+4 using LC-MS/MS. The median CEPM AUC0–48 in a cohort of 30 patients was 14.2 (14) mg·hr/L. The incidence of severe chronic graft-versus-host disease (GVHD) (73% vs. 11%, p  = 0.02), and GVHD-/relapse-free survival (GRFS) was significantly inferior in the CEPM AUC0–48 < 14 mg·hr/L group (54 days vs. 344 days, p  = 0.02). There was, however, no difference in grade III-IV acute GVHD (38% vs. 14%, p  = 0.12) and overall survival (295 days vs. not reached, p  = 0.2). CEPM AUC0–48, is associated with severe chronic GVHD and GRFS post-haplo-HCT in this exploratory study. There is scope for personalizing day + 4 PTCy dose based on day + 3 CEPM AUC0–8 .